Microchimerism in the transfused obstetric population. Issue 4 (16th July 2014) - Bloch, E. M.; Busch, M. P.; Lee, T.‐H.; Montalvo, L.; Matthews, Y.; Bird, A.; Bruhn, R.; Stefan, V.
<x xml:space="preserve">Abstract</x> Microchimerism (MC), the coexistence of allogeneic populations of cells within a host, is well described in pregnancy and blood transfusion. To date, transfusion‐associated MC (TA‐MC) appears unique to patients transfused after severe traumatic injury. We sought to determine whether transfusion in the peripartum period results in enduring, high‐level TA‐MC. We conducted a prospective cohort study of 22 women who were newly transfused within 48 h of delivery. Two subjects showed evidence of transient TA‐MC; however, MC was not detected at 6 weeks and 6 months. The negative findings suggest that enduring TA‐MC does not occur in this population.